2011
DOI: 10.5194/hessd-8-529-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling evaporation processes in a saline soil from saturation to oven dry conditions

Abstract: Thermal, suction and osmotic gradients interact during evaporation from a salty soil. Vapor fluxes become the main water flow mechanism under very dry conditions. A coupled nonisothermal multiphase flow and a reactive transport model of a salty sand soil was developed to study such an intricate system. The model was calibrated with data from an evaporation experiment (volumetric water content, temperature and concentration). The retention curve and relative permeability functions were modified to simulate oven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In porous medium saturated with saline solution that dries out by evaporation, the most prominent salt crystallization occurs at the matrix surface since this is where S1 takes place (Gran et al 2011;Nachshon et al 2011a, b;Or et al 2013;Rodriguez-Navarro and Doehne 1999). The precipitated salt results in physical changes of K (ψ), D e , and porosity (φ [m 3 /m 3 ]), as well as a possible reduction in the solution vapor pressure, P v [Pa], due to changes in the solution osmotic potential (e.g., Ho and Webb 2006).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In porous medium saturated with saline solution that dries out by evaporation, the most prominent salt crystallization occurs at the matrix surface since this is where S1 takes place (Gran et al 2011;Nachshon et al 2011a, b;Or et al 2013;Rodriguez-Navarro and Doehne 1999). The precipitated salt results in physical changes of K (ψ), D e , and porosity (φ [m 3 /m 3 ]), as well as a possible reduction in the solution vapor pressure, P v [Pa], due to changes in the solution osmotic potential (e.g., Ho and Webb 2006).…”
Section: Theorymentioning
confidence: 99%
“…Nevertheless, the liquid and vapor transport processes through these salt layers are far from being fully understood. Moreover, while the nature of efflorescent salt precipitation and its impact on evaporation have been widely studied (e.g., Gran et al 2011;Nachshon et al 2011a, b;Eloukabi et al 2013;Rad et al 2013;Mansoureh and Shokri 2014;Veran-Tissoires and Prat 2014), our understanding of subflorescent salt precipitation processes and their associated impact on porous medium evaporation is in its infancy. This could be related to the fact that NaCl, a very common salt in nature and the most common salt in our laboratories, precipitates as an efflorescent crust.…”
Section: Introductionmentioning
confidence: 99%
“…The layer of dry sand attenuates and dissipates part of the energy flux and induces some (strong) noise on the measurement. Moreover, water condensation below the matrix surface [Gran et al, 2011a[Gran et al, , 2011b] may decrease temperature difference between top sand surface and evaporation plane (at L cap ), which to some extent, reduces the simplification error. We also assume the column wall is an insulated boundary that does not let energy flow in or out of control volume.…”
Section: Thermography Of Evaporation In the Presence Of Salt Precipitmentioning
confidence: 99%
“…Although baseline studies have confirmed that soil salinity levels are high in the surface layer of the soil after evaporation (Fukuhara and Sato, 1994;Gran et al, 2011;Jalili et al, 2011), few empirical studies support the effectiveness of the scraping method for restoration of farmland. Only recently did Endo et al (2012) investigate the dynamics of soil salinity during evaporation in an application of the scraping method on land that had been affected by the tsunami after the Great East Japan Earthquake.…”
Section: Introductionmentioning
confidence: 98%